The multiliteracies project: preservice and inservice teachers learning by design in diverse content areas. (3rd July 2021) - Holloway, Susan M.
ABSTRACT: This study examines the experiences of preservice and inservice teachers who developed web platform posts for The Multiliteracies Project, which in part involved creating a multimodal pedagogical tool embedded in a lesson plan to explore a multiliteracies approach in diverse content areas. This research draws upon theory of Learning by Design to help articulate and evolve a multiliteracies theoretical framework. Using constructivist grounded theory, there were 37 participants over 3 years (2014–2017) who participated via face-to-face interviews, focus groups, and email responses. Document analysis and field notes were also used in the analysis. Three main themes that emerged from the data were: (i) Fostering Creativity through Design; (ii) Enhancing Disciplinary Literacy; (iii) Digital Literacies Broaden Pedagogy. The study found that while participants indicated they felt The Multiliteracies Project was demanding, they benefited from engagement in Learning by Design. From this study, education professors may further consider ways that they themselves might introduce the theory of Learning by Design into their work with preservice and inservice teachers to engage them in multiliteracies. This pilot study has led to the development of a nationally funded study which will expand the web platform and include interviews, in-depth observations, and original film footage of educators in secondary schools and adult community-based contexts.